1992
DOI: 10.3171/jns.1992.77.3.0360
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-early evaluation of regional cerebral blood flow in severely head-injured patients using xenon-enhanced computerized tomography

Abstract: The role of cerebral ischemia in the pathophysiology of traumatic brain injury is unclear. Cerebral blood flow (CBF) measurements with 133Xe have thus far revealed ischemia in a substantial number of patients only when performed between 4 and 12 hours postinjury. But these studies cannot be performed sooner after injury, they cannot be done in patients with intracranial hematomas still in place, and they cannot detect focal ischemia. Therefore, the authors performed CBF measurements in 35 comatose head-injured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
188
0
5

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 547 publications
(200 citation statements)
references
References 47 publications
7
188
0
5
Order By: Relevance
“…Marion, et al, in 1991, showed that cerebral blood flow was reduced after TBI in the first 12 -24 hours [8]. Bouma, et al, in 1992, showed that there was a 31.4% incidence of ischemia in the first 3.1h +/-2.1h after injury [11]. Chestnut, et al, in 1993, demonstrated that hypotension (BPsys < 90 mmHg) was associated with an increase in morbidity and mortality [3].…”
Section: Discussionmentioning
confidence: 99%
“…Marion, et al, in 1991, showed that cerebral blood flow was reduced after TBI in the first 12 -24 hours [8]. Bouma, et al, in 1992, showed that there was a 31.4% incidence of ischemia in the first 3.1h +/-2.1h after injury [11]. Chestnut, et al, in 1993, demonstrated that hypotension (BPsys < 90 mmHg) was associated with an increase in morbidity and mortality [3].…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that 2-CA was able to restore CBF only to the normal range early after severe injury. Early posttraumatic hypoperfusion is common in experimental and clinical TBI, and may mediate secondary damage (Yamakami and McIntosh, 1989;Bryan et al, 1995;Bouma et al, 1992); however, the optimal level of CBF early after injury is not known, and changes in metabolic demands are temporally complex. Kelly et al (2000), using a moderate CCI injury level, reported a marked initial increase in CMRglu, followed by metabolic depression by 3 h. Headrick et al (1994) reported that ICV administration of 5 nmol of 2-CA in rats attenuated the loss in phosphorylation potential at 2 to 4 h after fluidpercussion injury.…”
Section: Effect Of 2-chloroadenosine On Cerebral Blood Flow After Tramentioning
confidence: 99%
“…Traumatic brain injury (TBI) acutely reduces cerebral blood flow (CBF) in experimental models and humans (Yamakami and McIntosh, 1989;Bouma et al, 1992). This may mediate secondary damage, since posttraumatic metabolic demands are increased (Hovda et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…This is particularly true for studies involving stable xenon CT-CBF measurements [3][4][5] , besides less frequently used single photon emission computerized tomography (SPECT) CBF studies, which simply do not provide any metabolic information.…”
mentioning
confidence: 99%
“…In recent years, however, stable xenon computerized tomography (CT) CBF measurements became available, and a number of studies have emphatically and mistakenly addressed global or regional cere-bral ischemic changes in comatose patients [3][4][5] . The most elementary mistake in all these papers is that ischemia was defined as CBF levels of 18 ml/100 g/ min or less, based on previously reported work addressing ischemic changes at such CBF levels, but in the awake monkey brain 6 .…”
mentioning
confidence: 99%